Evaluating Bacillus flexus as bioremediators for ammonia removal in shrimp culture water and wastewater and characterizing microbial communities in shrimp pond sludge - Jasmin, M. Y.; Isa, N. Mat; Kamarudin, M.S.; Lim, K.C.; Karim, Murni (Springer Science and Business Media LLC, 2024)
The accumulation of nitrogen compounds in shrimp farming water and effluent presents a major challenge. Ammonia is a form of nitrogen that limits shrimp growth due to its potential toxicity and effects on shrimp health and water quality. This study is aimed at identifying promising bioremediators from shrimp pond sludge to mitigate ammonia levels in both culture water and wastewater and at determining major bacterial communities in sludge using metagenomic analysis. A sludge sample was collected from a shrimp pond in Selangor, Malaysia, to isolate potential ammonia-removing bacteria. Out of 64 isolated strains, Bacillus flexus SS2 showed the highest growth in synthetic basal media (SBM) containing ammonium sulfate at a concentration of 70 mg/L as the sole nitrogen source. The strain was then incubated in SBM with varying pH levels and showed optimal growth at pH 6.5–7. After 24 h of incubation, B. flexus SS2 reduced the ammonia concentration from an initial concentration of 5 to 0.01 mg/L, indicating a 99.61 reduction rate, which was highest in SBM at pH 7. Moreover, the strain showed ammonia removal ability at concentrations ranging from 5 to 70 mg/L. Metagenomic analysis revealed that Proteobacteria was the most abundant phylum in the sludge, followed by Cyanobacteria, Actinobacteria, Chloraflexi, Firmicutes, and Campilobacterota. Bacillus flexus SS2 belongs to the Bacillota phylum and has the potential to serve as a bioremediator for removing ammonia from shrimp culture water and wastewater.